Cultural transmission of animal tool use driven by trade-offs: insights from sponge-using dolphins - Ellen Jacobs; Chong Wei; Christine Erbe; Janet Mann (Royal Society Open Science)
Although tool use offers obvious benefits to the user, the role of costs in the spread of tool use has received scant attention. Sponge tool use is a foraging technique restricted to a small subpopulation of bottlenose dolphins (Tursiops aduncus) in Shark Bay, Australia, that carry basket sponges on their beaks to probe the seafloor and flush out camouflaged fish, widening the search area and protecting the beak from abrasion. While most instances of animal tool use extend the phenotype, we hypothesized that sponges interfere with echolocation, particularly reception of echoes along the lower jaw. To evaluate how echolocation signals change while travelling through sponge tissue, we simulated echolocation using finite-element analysis based on digital models of sponge species (Echinodictyum mesenterinum and Ircinia spp.). We find that acoustic properties of the echolocation signal are changed in the presence of Ircinia spp. and, to a lesser extent, E. mesenterinum. Given distortions vary with each sponge, dolphins must adaptively and flexibly compensate during neural signal processing. This explains why sponging takes so long to learn, is strictly vertically transmitted and does not spread to others despite close association with tool users. Taken together, these findings provide a compelling look at the underlying intrinsic and extrinsic forces shaping tool use in wild populations.